Redescriptions of species of Tetrarhynchobothrium Diesing, 1850 and Didymorhynchus Beveridge & Campbell, 1988 (Cestoda: Trypanorhyncha), with the description of Zygorhynchus borneensis n. sp - Beveridge, I. (Systematic Parasitology, 2008)
Tetrarhynchobothrium tenuicolle Diesing, 1850 is redescribed from the type-specimens collected from Raja clavata Linnaeus in the Adriatic Sea. T. striatum (Wagener, 1854) is redescribed from voucher specimens from the type host, Myliobatis aquila Linnaeus, from the type-locality, off Naples, Italy. The two species are very similar in tentacular armature, but are provisionally maintained as independent species, since the armature of T. tenuicolle cannot be fully described and because all available specimens of T. striatum are immature, limiting comparisons of potential differences in segment anatomy. T. setiense Dollfus, 1969 is treated as a synonym of T. striatum. Zygorhynchus borneensis n. sp. is described from Himantura uarnacoides (Bleeker) and H. pastinacoides (Bleeker) off Sabah, Malaysia. The new species is distinguished from its congeners by the very small hooks present in the basal region and by the presence of a uterine pore. The metabasal tentacular armature of Didymorhynchus southwelli Beveridge & Campbell, 1988, described for the first time, is homeoacanthous and homeomorphous in form. However, it has a basal swelling with hook rows originating on the bothrial surface and terminating on the antibothrial surface of the tentacle.